The Skinny on BMI-Based Hiring: An Assessment of the Legality and Effectiveness of Israel's Weight Restriction Law - Julie Gladstone (Washington University Global Studies Law Review, 2016)
There is nothing novel about ultra-thin models succumbing to eating disorders in the fashion industry. Legislative efforts to curb those disorders—and, by extension, to influence the body images of the general public—are, however, quite revolutionary. The Law for Restricting Weight in the Modeling Industry passed in the Israeli Knesset (Parliament) on March 19, 2012 and is the first law of its kind. The ban represents Israel’s response to rising rates of eating disorders and the potential link between exposure to images of ultra-thin models and poor body image of the consumer. This Note asserts that Israel’s Basic Law: Freedom of Occupation stands as an insurmountable hurdle to the future legality of the Weight Restriction Law. In light of recent decisions favoring the broad reach of the freedom of occupation, a potential legal challenge of the Law would ultimately end in its demise. Although the Israeli Knesset has carved out specific exceptions that allow for discriminatory hiring policies based on certain qualifications, the personalized assessments, the attenuated nature between the model’s well-being and the consumer’s safety, and the paternalistic nature of relieving models of responsibility for their own health would, if challenged, defeat the law as illegally discriminatory and restrictive of the freedom of occupation. Part I will provide some background on eating disorders as to their manifestations, symptoms, and prevalence in the modeling industry and beyond. Part II will track the link between the modeling industry and the increase in eating disorders as motivations for and explanations of the Weight Restriction Law. Part III will describe the relevant purposes and provisions of Israel’s Basic Laws that address whether or not a law such as the Weight Restriction Law will withstand a legal challenge. Part IV will demonstrate, by way of recent Basic Law: Freedom of Occupation litigation, how the Weight Restriction Law will be struck down as illegally restrictive of occupational freedom once challenged.
Keywords: Israel; International Law; Discrimination; Model